The Relationship Between Students’ Interaction And Online Learning Content - Adri Daswin (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to identify and understand the relationship between students’ interaction and online learning content. This research method is associative quantitative research, research that produces quantitative data which will later be used for processing survey data. obtained through observation and literature study. The results showed that the highest average value is found in the items